The wicked girls [compact disc, unabridged] - Marwood, Alex (Tantor Media, Inc., 2013)
On a fateful summer morning in 1986, two eleven-year-old girls meet for the first time. By the end of the day, they will both be charged with murder. Twenty-five years later, journalist Kirsty Lindsay is reporting on a series of sickening attacks on young female tourists in a seaside vacation town when her investigation leads her to interview carnival cleaner Amber Gordon. For Kirsty and Amber, it's the first time they've seen each other since that dark day so many years ago.